The Effect of Temporary Dumps (TPS) on the Health of the Environment Around the TPS Behind Tangsi Settlement, Padang Barat District - Rantika Maida Sahara; Chyntia Devi; Megawati; Aulia Zikra (Knowledge and Environmental Science for Living and Global Health, 2025)
Temporary Disposal Sites (TPS) play an important role in urban waste management, but their proximity to residential areas can trigger environmental and health problems. The TPS at Belakang Tangsi, Padang Barat, is directly adjacent to a densely populated settlement, making it a critical case to study. This research assessed its impact on environmental health using a quantitative descriptive approach, with data collected through observations, questionnaires from 75 residents, and interviews with sanitation workers and local officials. Descriptive statistics and relational analysis were applied to evaluate community perceptions and health concerns. Findings show that most residents reported foul odors, increased flies and rodents, and reduced comfort, with 68% experiencing direct disturbances and 53% expressing health concerns. These results highlight that poorly managed TPS near settlements not only degrade sanitation but also raise psychosocial stress and disease risk. The novelty of this study lies in documenting the specific impacts of an urban TPS located within dense residential areas, providing evidence for the urgent need to improve management, strengthen community-based waste sorting, and reconsider TPS placement in urban planning.